(untitled) (OODBODHAN, 2025)
Limited fossil fuel reserves led to a focus on alternative fuels for combustion engines. Several studies reported optimal (20%) of biodiesel blend for utility in compression ignition engines. Existing research offers limited insights into how varying compression ratios (VCR) affect engine performance when jatropha biodiesel blends. This study investigates the influence of three compression ratios (15:1, 16:1, and 17:1) on the performance, combustion and emission characteristics of compression ignition engines fueled with a 20% jatropha biodiesel-diesel blend (JB20) under different loading conditions with a constant speed of 1500 rpm at injection pressure of 210 bar and injection timing of 230 bTDC. Jatropha biodiesel was produced from jatropha seed oil following two step transesterification process using methanol, sulphuric acid and sodium hydroxide and thus produced biodiesel was characterized by ASTM and Fourier-transform infrared spectroscopy (FTIR) to conform the desirable properties. The experimental results confirms that the performance, combustion and emissions properties improved to increase in compression ratio (CR) for both test fuels. It is found that increase in CR increases the Brake Thermal Efficiency (BTE) by 9.6%, Mechanical efficiency (ME) by 5.5%, Net Heat Release (NHR) by 17%, Peak Cylinder Pressure (PCP) by 20%, and reduces Specific fuel Consumption (SFC) by 11%, Exhaust Gas Temperature (EGT) by 17% with increase in CR from 15 to 17 for JB20 at 3.k kW brake power (BP). Also JB20 shows reduction in emissions of hydrocarbon, carbon monoxide and smoke opacity to be 9.5%, 14% and 31% compared to diesel. Thus inferred that JB20 fuel performed well at high compression ration without any design modifications.